Combined effects of high temperature and light on the photosynthetic parameters and recovery of temperate microphytobenthos in Browns River, Tasmania. (21st September 2022) - Salleh, Sazlina; McMinn, Andrew
Abstract: Microphytobenthos (MPB) communities are responsible for most primary production in shallow intertidal mudflats. The effects of short-term changes in temperature and light (1200, 500 and 0 μmol photons m −2 s −1 ) on the photosynthetic activity of intertidal MPB communities of Browns River, Tasmania, during winter (0, 5, 10 and 15°C) and summer (20, 25, 30, 35 and 40°C) were examined using a Pulse Amplitude Modulated (Water PAM) fluorometer. The MPB communities were primarily dominated by the diatom genera Navicula, Cocconeis and Amphora, with a difference in species dominance during seasons. During summer, Amphora coffeaeformis dominated communities were significantly impacted by temperatures above 30°C regardless of light intensities. The MPB was able to photosynthesize at temperatures only up to 25°C. The rETRmax at 25°C, ranged from 39.18 ± 3.42 (500 μmol photons m −2 s −1 ) to 22.83 ± 1.05 (0 μmol photons m −2 s −1 ), which was lower than the values recorded at an equivalent irradiance in in-situ summer. However, if ambient temperature exceeds 25°C in summer, it is likely that the photosynthetic capabilities of the MPB will be diminished and it will cause irreversible photoinhibition.